THE INFLUENCE OF THE SNOWBALL THROWING COOPERATIVE LEARNING MODEL ON LEARNING OUTCOMES SDN 4 BANAWA - Pahriadi Pahriadi; Supriyatman Supriyatman; Mirnawati Mirnawati (Universitas Tadulako, 2020)
This study aims to determine the effect of the snowball throwing learning model on science learning outcomes of fourth grade students of SDN 4 Banawa. The problem examined in this study is whether there is an influence on the snowball throwing learning model on the science learning outcomes of fourth grade students at SDN 4 Banawa ? The population in this study were all fourth grade students of SDN 4 Banawa with a total of 43 people and the sample in this study consisted of two classes namely class IVa and class IVb. This research is a quantitative study using the snowball throwing learning model using two groups, namely the experimental class group and the control class group. The design used in this study is the Pretest-Posstest Control Group Design. The instrument used in this study is a test of learning outcomes in the form of multiple choice. The average results of pretest data processing obtained in the experimental class is 4.41 and posttest score is 8.55 while the average score of the pretest obtained in the control class is 3.69 and the posttest score is 7.45. Based on the results of testing the hypothesis obtained t-counted = 2.35 and t table = 1.68 at the real level α = 0.05 with criteria if t-counted t-table then Ha is accepted and H0 is rejected, based on the results of the hypothesis test it can be concluded that there is influence Snowball Throwing learning model for the science learning outcomes of fourth grade students of SDN 4 Banawa.